Radial Modification Design of Triple Arc Tooth Profile of Flexspline on Uniformly Distributed Spatial Backlash based on Harmonic Gear - Zhongfu Cheng; Jingzhong Xing; Liteng Shi; Xiaoxia Chen (Jixie chuandong)
For better meshing status between spatial tooth profile of flexspline machined by radial modification of the tool and the planar tooth profile of circular spline，a design method for radial modification of flexspline tooth profile is proposed. The radial and circumferential positions of flexspline teeth under the action of elliptic wave generator are obtained by using the exact algorithm of flexspline assembly deformation，then backlash is obtained by the backlash algorithm between circular arc tooth profiles. According to the assumption of the straight-line generator，the positioning of the teeth profiles and backlashes in several cross sections are determined，then the backlash is obtained to reveal the spatial backlashes distribution in the cross-sections along the axial direction of flexspline with tapered deformation. The backlash distribution without radial modification shows that the backlash of the conjugated tooth profile of circular spline designed with conjugated meshing theory is very small and uniform in the design cross section，and serious interferences occur in the front and back sections. Inward modification of the cutting tool in the front and back sections can eliminate the interference. Reasonable radial modification designed iteratively achieves the optimal backlashes approaching zero in all cross sections，and realize a line meshing state from the front to the back sections. The simulation of meshing trajectory shows that the reasonable radial modification can achieve a better meshing state between tooth profiles.